Stay Awareness with Fun: “Hit the Viruses” Game App - Shiau Gee, Lilian Lee (Multidisciplinary Applied Research and Innovation, 2022)
Along with increased self-awareness and preventive knowledge, each individual’s health should be optimised to mitigate the dangers posed by COVID-19. As a result, the project is intended to develop a digital game called "Hit the Viruses" to raise awareness and value of COVID-19 prevention measures with a hygiene and sanitation approach through exploration and intervention game-based learning. "Hit the Viruses" is an application game aimed at promoting knowledge and information development, particularly among children, by emphasising pandemic awareness in an engaging and innovative manner. Through the "learn while playing" method, the game aims to assist children in digesting complex scientific information about the virus while also increasing their knowledge of COVID-19 protective measures such as how to wear masks and sanitation requirements. The game is platform-based and includes 12 game levels; the visual style is simple 2D, and children take on the role of the game’s main character by navigating the game environment safely and accomplishing tasks such as collecting masks, soap, and sanitation. The Standard Operating Procedure (SOP) information incorporated into the design of this game is supposed to aid players in recalling it, hence establishing a favourable attitude toward COVID-19 transmission prevention awareness. Not only can learning about gaming scenarios assist improve awareness, but it’s also a terrific way to spend time indoors with family. The game is intended to educate the public about the precautions that must be followed during the COVID-19 outbreak. This game has implications for strategy, practise, and research, with the primary goal of educating people about viral transmission avoidance.